2017
DOI: 10.1093/mnras/stx2153
|View full text |Cite
|
Sign up to set email alerts
|

A search for optical bursts from the repeating fast radio burst FRB 121102

Abstract: We present a search for optical bursts from the repeating fast radio burst FRB 121102 using simultaneous observations with the high-speed optical camera ULTRASPEC on the 2.4-m Thai National Telescope and radio observations with the 100-m Effelsberg Radio Telescope. A total of 13 radio bursts were detected, but we found no evidence for corresponding optical bursts in our 70.7-ms frames. The 5-σ upper limit to the optical flux density during our observations is 0.33 mJy at 767nm. This gives an upper limit for th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(111 citation statements)
references
References 47 publications
6
101
1
Order By: Relevance
“…Multi-wavelength observations also searched for prompt optical, X-ray and γray flashes associated with the radio bursts. No optical pulses were found in a campaign where the 2.4-m Thai National Telescope was shadowed by Effelsberg and 13 radio bursts were detected (Hardy et al, 2017). Similarly, despite the detections of multiple radio bursts, no prompt X-ray or γ-ray bursts were found in observations with simultaneous radio and Chandra, XMM-Newton, Swift, and Fermi coverage.…”
Section: Frb 121102mentioning
confidence: 88%
See 1 more Smart Citation
“…Multi-wavelength observations also searched for prompt optical, X-ray and γray flashes associated with the radio bursts. No optical pulses were found in a campaign where the 2.4-m Thai National Telescope was shadowed by Effelsberg and 13 radio bursts were detected (Hardy et al, 2017). Similarly, despite the detections of multiple radio bursts, no prompt X-ray or γ-ray bursts were found in observations with simultaneous radio and Chandra, XMM-Newton, Swift, and Fermi coverage.…”
Section: Frb 121102mentioning
confidence: 88%
“…To date, FRBs have only been detected in the radio band 5 ; no contemporaneous optical, X-ray or gamma-ray flash has been detected (e.g., Scholz et al, 2017;Hardy et al, 2017). This currently leaves us in the situation where we need to maximize what we can learn from the properties of the radio pulses themselves.…”
Section: Propagation Effectsmentioning
confidence: 99%
“…where L c is the peak luminosity and σ L is the standard deviation of log L. This last assumption is based on the luminosity distribution statistics of 227 bursts detected from FRB 121102 (Spitler et al 2014(Spitler et al , 2016Scholz et al 2016Scholz et al , 2017Law et al 2017;Hardy et al 2017;Spitler et al 2018;Michilli et al 2018;MAGIC Collaboration et al 2018;Zhang et al 2018;Hessels et al 2019;Gourdji et al 2019), as shown in Fig. 1.…”
Section: Non-detection Probabilitymentioning
confidence: 99%
“…So far, only two repeating FRBs have been reported in the literature, FRB 121102 (Spitler et al 2016;Scholz et al 2016) and FRB 180814 (Amiri et al 2019). Searching for GRBs from archival Fermi data have been carried out for these two sources with null results (Yamasaki et al 2016;Zhang & Zhang 2017;Xi et al 2017;Yang et al 2019;Guidorzi et al 2019). We adopt an opposite approach.…”
Section: Introductionmentioning
confidence: 99%
“…http://dwfprogram.altervista.org/ 4Hardy et al (2017) report upper limits on optical flux at times coincident with bursts from the repeating FRB 121102. The extremely fast cadence of Thai National Telescope/ULTRASPEC (70.7 ms frames) makes their results meaningful, however we caution that i) possible optical emission could have been fainter than…”
mentioning
confidence: 99%